ニシ オングルトウ オオイケ ヨリ エタ ケイソウ - 福島, 博; フクシマ, ヒロシ; 綿貫, 知彦; ワタヌキ, トモヒコ; 小林, 艶子; コバヤシ, ツヤコ; FUKUSHIMA, Hiroshi; WATANUKI, Tomohiko; KO-BAYASHI, Tsuyako (国立極地研究所, 1974)
P(論文) In this paper are reported 15 taxa of diatom. Among these taxa, Amphora holsatica HUST., Amphora veneta KUTZ., Gomphonema angustatum (KUTZ.) RABENH., Navicula mutica KUTZ. Var. goeppertiana (BLEISCH) GRUNOW, Navicula muticopsis van HEURCK var. muticopsis f. murrayi (W. & G. S. WEST) KO-BAYASHI, Navicula simplex KRASSKE, Navicula sp., Nitzschia dubia W. SM. Var. australis M. PERAGALLO, Pinnularia cymatopleura W. & G. S. WEST and Stauroneis perminuta GRUNOW were observed on Ongul Island for the first time. departmental bulletin paper